2012
DOI: 10.1007/s12564-012-9205-1
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide comparative study between private and public university students’ soft skills

Abstract: The main function of Higher Educational Institutions (HEIs) is to produce skilled and knowledgeable workforce who are able to not only function with minimal guidance but also to contribute effectively to the hiring organizations. Many studies have indicated that most HEIs have somewhat similar course content and thrived at producing students with good academic achievement. But what differentiated them from one another is their ability to develop knowledge workers with the right employability skills or 'soft sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 5 publications
0
12
0
3
Order By: Relevance
“…A study by Hazilah et al (2013) mentioned that among the comments made by employers on new graduates, there is a lack of communication skills in the workplace and the inability to present information clearly. To address the above problems of inadequacy in relation to specific elements of generic skills, especially among girls, Abdul Malek et al (2012) suggested that girls should be encouraged to assume leadership roles not only in classroom presentations but also in extra-curricular projects. This is in addition to engaging them in problem-based learning projects, case studies and industrial attachments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Hazilah et al (2013) mentioned that among the comments made by employers on new graduates, there is a lack of communication skills in the workplace and the inability to present information clearly. To address the above problems of inadequacy in relation to specific elements of generic skills, especially among girls, Abdul Malek et al (2012) suggested that girls should be encouraged to assume leadership roles not only in classroom presentations but also in extra-curricular projects. This is in addition to engaging them in problem-based learning projects, case studies and industrial attachments.…”
Section: Discussionmentioning
confidence: 99%
“…However, in general, boys are said to have obtained higher levels of generic skills compared to girls. A large-scale national level study by Abdul Malek et al (2012) involving 10,140 students in both Malaysian public and private universities pointed out that boys outperformed girls in all generic skills except in teamwork and moral and professional ethics. The study attributed this finding to the boys' inclination to individualistic traits and aggressiveness which caused their lower scores in team-work.…”
Section: Gender Differences In Generic Skills and Learning Approachesmentioning
confidence: 99%
“…Despite these limitations, this study addresses the lack of knowledge about social work student competency in China and provides practical implications to foster these competencies. One role of higher educational institutions is to produce a skilled and knowledgeable workforce that not only functions with minimal guidance, but also contributes effectively to potential employers (Abdul Karim, et al, 2012). What Chinese social work students obtain in school forms the foundation of their professional identity and workforce competency.…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 99%
“…In Malaysia, youth face employability challenges due to the lack of required soft skills (Abdul Karim et al, 2012;Awang-Hashim, et al, 2015;Pillai, Khan, Ibrahim, & Raphael, 2011;Zaharim, Ahmad, Yusoff, Omar, & Basri, 2012). According to a press release dated 29 May 2012 on the website of the Economic Planning Unit (EPU) of the Prime Minister's department (http://www.epu.gov.my/en/sl1m), tracer studies by the Ministry of Higher Education (MOHE) found that most of the 20% of graduates who did not secure employment within six months of graduation were underprivileged.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2015 Graduate Tracer Study Report Ministry of Higher Education, 2016, 42% of unemployed recent graduates were from families earning a monthly household income of RM1,000 and below, followed by 34.8% from families with a monthly income of between RM1,001 and RM2,000, and 27.1% from families with a monthly income of between RM2,001 and RM3,000. As for the soft skills of graduates, the literature suggests that Malaysian tertiary education institutions should play a role in developing them, as these institutions provide the final level of formal education before graduates enter the workplace (Abdul Karim et al, 2012;Esa, Padil, Selamat, & Idris, 2015;Idrus, Dahan, & Abdullah, 2009& 2014Musa, Mufti, Latiff, & Amin, 2012;Nikitina & Furuoka, 2012).…”
Section: Introductionmentioning
confidence: 99%